PENGARUH BI’AH LUGHOWIYAH TERHADAP KEMAMPUAN BERBICARA BAHASA ARAB DI SMP QURAN DARUL IKHLAS PRINGSEWU: Indonesia - Abdul Sabri, Muhammad; Khoirul Ma'arif, Amrulloh; Hamid, Abdul (STIT Pringsewu, 2023)
Abstract Bi'ah lughowiyah is a factor that supports language acquisition and language learning, these two things can develop well when the environment provides language learning facilities and language skills. This study aims to determine how much influence bi'ah lughowiyah has on the ability to speak Arabic at SMP Quran Darul Ikhlas Pringsewu. This study aims to determine how much influence bi'ah lughowiyah has on the ability to speak Arabic at SMP Quran Darul Ikhlas Pringsewu.This research is quantitative research by taking a sample of 63 students of class VIII and class IX SMP Quran Darul Ikhlas Pringsewu. The method of collecting data in this study is using observation, questionnaires and documentation. In this study, two variables were used, namely bi'ah lughowiyah as the dependent variable (X) and speaking ability independent variable (Y).Research instrument analysis includes validity and reliability tests. The data analysis used is simple regression analysis. The results of this study indicate that Bi'ah Lughowiyahin SMP Quran Darul Ikhlas Pringsewu is quite good with a percentage of 62.1%. Meanwhile, the ability to speak Arabic for Darul Ikhlas Quran Middle School students is also quite good with a percentage of 60.5%. Based on the data analysis performed using simple regression analysis, there is a significant influence between bi'ah lughowiyah on the ability to speak Arabic. With a calculated T value = 5.472 greater than T table = 1.99962 and a sig probability value of 0.000 <0.05 then Ho is rejected and Ha is accepted. So that the influence of bi'ah lughowiyah (X) on the ability to speak Arabic (Y) at SMP Quran Darul Ikhlas Pringsewu, namely 57.4%, means that it is included in the level of influence of